2007
DOI: 10.1021/jp074707k
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic O2 Evolution of Rhodium and Antimony-Codoped Rutile-Type TiO2 under Visible Light Irradiation

Abstract: The effects upon the photophysical and photocatalytic properties of the codoping of rhodium and antimony in rutile-type TiO2 were investigated. TiO2 codoped with rhodium and antimony (TiO2:Rh/Sb) had an absorption band in the visible light region. Its energy gap was 2.1 eV. The TiO2:Rh/Sb powder showed photocatalytic activity for the oxidation of water to form O2 in the presence of Ag+ ions as an electron acceptor under visible light irradiation (λ > 440 nm), whereas TiO2 doped with only rhodium showed no acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
123
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(134 citation statements)
references
References 35 publications
(84 reference statements)
10
123
0
Order By: Relevance
“…On the other hand, Niishiro et al reported that rutile-type TiO2 codoped with Rh and Sb showed high photocatalytic O2 evolution from an aqueous silver nitrate solution under visible light irradiation. 22) According to their report, the activity depended upon suppressing the formation of Rh 4+ and promoting the formation of Rh 3+ by codoping high-valence ions, such as Sb 5+ . In addition, codoping with Rh and Sb suppressed the formation of oxygen defects, which act as recombination centers.…”
Section: +mentioning
confidence: 99%
“…On the other hand, Niishiro et al reported that rutile-type TiO2 codoped with Rh and Sb showed high photocatalytic O2 evolution from an aqueous silver nitrate solution under visible light irradiation. 22) According to their report, the activity depended upon suppressing the formation of Rh 4+ and promoting the formation of Rh 3+ by codoping high-valence ions, such as Sb 5+ . In addition, codoping with Rh and Sb suppressed the formation of oxygen defects, which act as recombination centers.…”
Section: +mentioning
confidence: 99%
“…4(a) , which results in the formation of finer and smoother crystalline particles. 28 However, in our case, the doping of 0.3 at.% Pt 2+ (0.94 Å ) does not significantly change either the size of particle or the morphology [ Fig. 4(b)].…”
Section: Photocatalytic Activity Measurementsmentioning
confidence: 49%
“…[24][25][26][27][28] Ahmad et al reported that Sc and Nb codoped TiO 2 nanoparticles are relatively more photoactive for 2-chlorophenol degradation under visible light than the particles doped with Sc or Nb alone. 25 Kato ) and TiO 2 codoped with Rh 3+ and Sb 5+ were also shown to improve photocatalytic activity for O 2 evolution under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kitano et al [13] showed that Rh modified TiO 2 samples exhibit higher level of activity than Cu 2+ modified and the nitrogen-doped samples. On the other hand, Niishiro et al [14] reported that TiO 2 doped with only Rh shows only negligible photocatalytic activity as it creates Rh 4+ ions. They suggested that in such cases, charge compensated codoping with pentavalent ions such as Sb 5+ , Nb 5+ , Ta 5+ becomes necessary for suppressing the formation of Rh 4+ ions and improving photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%